Non-clinical Covid19 diagnosis on CT-scan, Chest X-ray, and respiratory patterns using deep-learning and signal processing - Tasnim, Sadia; Sarker, Sukarna; Bhoumik, Partha; Al Maruf, K.M. Abdullah; Rahman Hasib, MD Mahfuzur (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.